Habitat Characteristic of Oryzias matanensis Aurich in Towuti Lake - Eragradini, Athira Rinandha; Omar, Sharifuddin Bin Andy; Tresnati, Joeharnani (Journal La Lifesci, 2024)
Lake Towuti, one of the ancient lakes in Indonesia, is the second largest freshwater lake after Lake Toba. One of the endemic fish that live in Lake Towuti is the Matano Medaka fish (Oryzias matanensis Aurich, 1935). Due to land change, Lake Towuti's indicate is in threat of declining, which potentially have an impact on the endemic fish's habitat. The aim of this study is to identify the habitat characteristics of Lake Towuti. The data collected in this study includes temperature, pH, dissolved oxygen, and aquatic plants. Sampling was carried out in the morning, starting at 8:00 WITA and ending at 11:00 WITA at two different stations. Station selection was carried out based on differences in habitat, the presence of aquatic plants, and the presence of fish samples. Habitat characteristics at station one are marked by the number of water plants with the basic substrate types of sand, mud, and stones. In contrast, at station two, it is characterized by the absence of water plants and the basic substrate types of sand, rock, and gravel. Ecological aspects, including water physics and chemistry parameters, did not experience large fluctuations during the study period. The water conditions at each research station were not significantly different, so the water conditions were still good and supported the fish life in Lake Towuti.